Implementation of Medan City Government Policies in Overcoming Traffic Congestion and Density (Case Study of Traffic Intersection, Medan Tembung District) - Sahputra, Dimas; Hidayat Rastami, M Ilham; Damanik, Denada; Ivanna, Julia (PT. Berlian Pustaka Indonesia, 2023)
This research was conducted to find out that transportation development aims to improve efficient, effective, reliable, quality, safe, affordable transportation services. Realizing integrated national transportation with regional development, a distribution system that can provide community services, increasing adequate rural-urban networks (RPJM Dirjendat Kemenhub RI). The method used in this research is literature study in which information is obtained from various reading sources such as books, journals, and websites that are still related to research studies. The results of this study are the way Pemko Medan in overcoming traffic jams that occur in Medan City, especially traffic jams that occur at Simpang Aksara, Medan Tembung District based on applicable laws